Faktor-Faktor Yang Mempengaruhi Motivasi Bidan Pelaksana Dalam Pelayanan Ibu Nifas Di Wilayah Kabupaten Blora - Epi Saptaningrum; Sutopo Patria Jati; Anneke Suparwati (Jurnal Manajemen Kesehatan Indonesia, 2016)
Maternal Mortality Rate mostly occurred during postnatal period. Midwives played an important role and had responsibility in providing maternal services. Postnatal services in Blora District had not been optimally implemented. This condition was influenced by motivation of midwives in providing postnatal services. Five of seven midwives said that they were lazy to provide postnatal services particularly in visiting maternal. Motivation was influenced by intrinsic and extrinsic factors. Therefore, factors influencing motivation of midwives in providing maternal services needed to be investigated. This was a quantitative-analytic study using cross sectional approach. Data were collected using a questionnaire. Number of population was 359 midwives in Blora District. Number of samples were 76 respondents calculated using minimal sample size. A validity test used pearson product moment whereas alpha Cronbach test was used to analyse reliability. Data were analysed using methods of univariate (Kolmogorov-Smirnov test), bivariate (Chi-Square test), and multivariate (logistic regression test). The results of this research showed that factors of perception of administration and policy (p=0.043; C=0.227), perception of supervision (p=0.001; C=0.346), perception of work (p=0.000; C=0.503) and perception of environmental condition (p=0.001; C=0.350) statistically significantly related to motivation of midwives. Perception of work was the most influenced factor of motivation (p=0.000; Exp(B)=11.655). As suggestions, other researchers need to investigate the factor of perception of work. District Health Office needs to evaluate main and additional tasks and to consider increasing incentive for activities of maternal services. Indonesian Midwives Association of Blora needs to guide and to improve motivation of midwives in providing maternal services. Health Centres (Coordinator Midwives) need to involve midwives in improving perception of work (maternal services) by conducting training.